"This is not a drill": Activation of a student-led influenza vaccination point of dispensing. Issue 2 (17th February 2019) - Adams, Lavonne M.; Canclini, Sharon; Tillman, Kelle
ABSTRACT: Objective : To describe activation of a Point of dispensing (POD) in response to an influenza outbreak, highlighting the use of a student-led model.Participants : Faculty, staff, and students of Harris College of Nursing and Health Sciences, Texas Christian University (TCU), as well as those located in its primary building.Methods : In response to an August 2017 influenza outbreak, a vaccination clinic was conducted for a target population through POD activation. The larger campus community was served through provision of additional doses by the Texas Christian University Health Center and the annual October student-led vaccination clinic.Results : Eleven additional cases were diagnosed after vaccinations began.Conclusions : One hundred percent of the targeted population was vaccinated (n = 824), with an additional 127 participants vaccinated (others working in the building where POD held also vaccinated). This was the first time POD activation had occurred on campus in response to an outbreak.